Knowledge, perception and attitude of physiotherapy and medical undergraduates in Nigeria towards people with disability (2022)
Background: Knowledge, perception and attitude of healthcare professionals could constitute barriers that could affect healthcare provision for, and social life of People with Disability (PWD). Knowledge, perception and attitude towards PWD was investigated among physiotherapy and medical undergraduates of the University of Ibadan, Nigeria using a mixed-method design. Methods: Knowledge and perception of first and final year physiotherapy and medical undergraduates about PWD were assessed using a validated questionnaire while attitude was assessed using the Attitude Towards Disabled Persons scales (Forms A and O). Focus Group Discussion (FGD) was held with eight purposively selected students from the survey sample. Data were analysed using Man- Whitney U test at p-value <0.05. Transcripts from the discussion were analysed thematically. Results: 187 undergraduates (106 males) aged 20.35+2.67years participated in the survey. Majority of the participants (≥88.0%) were knowledgeable about physical disabilities but had poor perception and negative stereotypes about PWD. Only 38(20.3%) of the participants reported that PWD experienced disparities in accessing healthcare. First- year physiotherapy undergraduates had more positive attitudes towards PWD than first-year medical students (68.2% vs 35.0%, p<0.01) whereas final year medical students had more positive attitude that final year physiotherapy students (68.2% vs 52.6%, p=0.29) on form O. Participants in the FGD believed disability could be socially constructed and not just on account of physical impairments. They considered treating PWD as being more stressful than treating people without disability. Conclusion: Participants had good knowledge, ambivalent attitude and poor perception about PWD. Their perception and attitude could be improved through adequate exposure and contact with PWD.